Restorative Justice Elements in Lithuanian Criminal Law: Implementation Challenges: - - Michailovič , Ilona; Povilanskas, Mindaugas (Kriminologijos studijos, 2025)
The article discusses the main criminal legal instruments containing elements of restorative justice and the obstacles to their implementation in the Lithuanian criminal justice system. The main attention is paid to the analysis of the release from criminal liability upon the victim-offender reconciliation and the penal order as an instrument of criminal proceedings. Based on scientific sources and case law, the analysis of the elements of restorative justice is carried out in comparison with the institute of penalty negotiation between the prosecution and defence parties, in the light of Article 39¹ of the Criminal Code. In the context of the purpose of criminal proceedings, the article also discusses the obstacles to the development of mediation. Although certain elements of restorative justice exist in the Lithuanian criminal justice system, in order to achieve the restoration of social peace and the implementation of mediation in criminal cases, not only are amendments to criminal laws necessary, but also increasing awareness of mediation and its advantages.
Keywords: restorative justice; mediation; release from criminal liability upon the victim-offender reconciliation; penal order; penalty negotiation; social peace